PANDANGAN MASYARAKAT ADAT TENTANG MEMUDARNYA ADAT TEMETOK DALAM WALIMAH AL-URSY STUDI DI KECAMATAN GUNUNG MERIAH KABUPATEN ACEH SINGKIL - Sulaiman Tamba, Gus Herlina (Taushiah: Jurnal Hukum, Pendidikan dan Kemasyarakatan, 2022)
This research raises the title of Indigenous People's Views About the Fading of the Temetok Indigenous in Walimah AL-Ursy (Case Study in Gunung Meriah District, Aceh Singkil Regency). Walimah is a form of gratitude by inviting relatives, neighbors and people around, knowing that a man and a woman are married and avoid slander. Temetok is a community tradition in Gunung Meriah District, Aceh Singkil Regency. As is well known, in its application, Temetok is a gift, grant, gift, or alms between individuals with the intention of walimatul 'ursy. But what happens in society, Temetok has a different meaning from the actual meaning. Most people call a debt deal. The purpose of this study is to reveal the meaning of Temetok in Walimah Al-Ursy according to the views of indigenous peoples towards temetok in Gunung Meriah District, Aceh Singkil Regency. The method used in this research is field research, which is descriptive in nature by obtaining data from observations, interviews, and documentation. Then proceed to the editing and analysis process. The results of this study indicate that the Temetok tradition that developed in the people of Gunung Meriah District is starting to fade because of economic factors.